La Vision artistique de la montagne : panorama, pli ou plongée ? - Marie-Madeleine Martinet (Anglophonia)
Mountains as a new artistic subject gave rise to original modes of artistic vision, simultaneously providing answers to current questionings on spatial perception. Thus panoramic views offered an option suited to mediating the experience of travellers surrounded by summits. The undulations of uneven grounds provided motifs to represent folded spaces where diversity or surprise predominates over regularity; the reflections of these tormented shapes between glaciers became an object of scientific investigation, at the same time inspiring romantic landscape painters to find new shades of colour. Lastly, the vertical dimension, angled views and peaks, brought a new approach to perspective and the corresponding optical illusions.Mountains, a strange world, brought about inverted visual effects with the most irregular shapes prevailing over landscapes; and they were first studied in distant countries where their unusual appearance seemed less unexpected, before being discovered at home as an artistic subject